Discrepancies Between Osteoporotic Fracture Evaluations in Men Based on German (DVO) Osteoporosis Guidelines or the FRAX Score - Witzel, J C; Giessel, A; Heppner, C; Lamersdorf, A; Leha, A; Glüer, C C; Siggelkow, H (Experimental and Clinical Endocrinology & Diabetes, 2023)
Introduction Established scores estimate 10-year fracture risk in osteoporosis to assist with treatment recommendations. This study compared the risk probabilities of major osteoporotic and hip fractures calculated by the FRAX tool with those of the DVO score, established in German-speaking countries.Material and Methods This seven-year retrospective study analyzed data of 125 male patients (mean age: 59.2±10.7 years) evaluated for osteoporosis. For the DVO score, the therapy threshold of>30% for vertebral and hip fractures suggested by DVO guidelines was implemented. We calculated fracture risks based on FRAX scores with aBMD and applied a common therapy threshold of≥3% for hip fracture and subsequently determined the “DVO-equivalent risk level” for FRAX-based assessment that would identify as many male patients as identified by the DVO score.Results Based on DVO score, 60.0% of patients had a 10-year risk of hip and vertebral fractures>30%. The recommendations for individuals based on FRAX scores for hip fracture with aBMD with risk≥3% overlapped with those based on DVO score in 36% of patients. Patients identified for treatment only by DVO score presented a higher percentage of spine fractures (65 vs. 41%). The thresholds for this “DVO-equivalent risk level” for ‘FRAX with aBMD’ was estimated to be≥6.7% for major osteoporotic fracture and≥2.1% for hip fracture.This study demonstrates that the DVO score was more sensitive than the FRAX score for patients with prevalent spinal fractures. We suggest considering the appropriate score and therapy threshold carefully in the daily care of male patients.
Keywords: bone mineral density; therapy threshold; osteoporosis risk factors; secondary osteoporosis; 10-year fracture risk